Learning Pali Language Application: Learning Pali Language Application - Peykaeo, Rangsey; Triamwitthaya, Suthep; Taileelais, Kamolrat; Pandee, Phromphong (Journal of MBU Humanities, 2022)
This academic paper on learning Pali by using the app. There objectives to study are 1) to study Pali language through applications and to present innovations in learning Pali language through applications at present, learning has been developed from studying in the classroom. Studying outside the classroom and online studying through applications enable students to learn at anytime and anywhere in the world but students must have smartphones that can connect to the Internet and they will be able to learn things easily and quickly this can respond to the behaviors of recipients in the present resulting in unlimited learning students can develop their knowledge, including language potential which makes them understand the teachings of the Buddha more completely students apply the teachings of the Lord in their daily lives for further development of themselves and others